Investment without Democracy : Ruling-Party Institutionalization and Credible Commitment in Autocracies - Gehlbach, Scott; Keefer, Philip (2012)
What explains private investment in autocracies, where institutions that discourage expropriation in democracies are absent? We argue that institutionalized ruling parties allow autocrats to make credible commitments to investors. Such parties promote investment by solving collective-action problems among a designated group, who invest with the expectation that the autocrat will not attempt their expropriation. We derive conditions under which autocrats want to create such parties, and we predict that private investment and governance will be stronger in their presence. We illustrate the model by examining the institutionalization of the Chinese Communist Party.